Teacher’s Productivity in Promoting Quality Education in Public Primary Schools in Kenya - Kirimi, Josephine Kagwiria; Amukowa, Wyclife O. (MCSER-CEMAS-Sapienza University of Rome, 2013)
Researchers and policy makers agree that teacher quality is a pivotal issue in education. Quality education begins with quality teachers. Excellent teachers do more than teach the curriculum content: they inspire and enthuses their pupils and serve as role models in terms of attitudes and social relationships. This paper discusses factors that may affect the productivity of teachers in promoting the quality of education in Kenya.
Keywords: Quality; Education; Teachers; Schools; Productivity